Anticancer Therapy-Induced Atrial Fibrillation: Electrophysiology and Related Mechanisms - Yang, Xinyu; Li, Xinye; Yuan, Mengchen; Tian, Chao; Yang, Yihan; Wang, Xiaofeng; Zhang, Xiaoyu; Sun, Yang; He, Tianmai; Han, Songjie; Chen, Guang; Liu, Nian; et al. (Frontiers in Pharmacology, 2018)
Some well-established immunotherapy, radiotherapy, postoperation, anticancer drugs such as anthracyclines, antimetabolites, human epidermal growth factor receptor 2 blockers, tyrosine kinase inhibitors, alkylating agents, checkpoint inhibitors, and angiogenesis inhibitors, are significantly linked to cardiotoxicity. Cardiotoxicity is a common complication of several cancer treatments. Some studies observed complications of cardiac arrhythmia associated with the treatment of cancer, including atrial fibrillation (AF), supraventricular arrhythmias, and cardiac repolarization abnormalities. AF increases the risk of cardiovascular morbidity and mortality; it is associated with an almost doubled risk of mortality and a nearly five-fold increase in the risk of stroke. The occurrence of AF is also usually researched in patients with advanced cancer and those undergoing active cancer treatments. During cancer treatments, the incidence rate of AF affects the prognosis of tumor treatment and challenges the treatment strategy. The present article is mainly focused on the cardiotoxicity of cancer treatments. In our review, we discuss these anticancer therapies and how they induce AF and consequently provide information on the precaution of AF during cancer treatment.